The Dietary Stories of One Household: Multi-proxy Study of Food Remains at Dominikonų St. 11 in Vilnius Between 15th-18th Century - Karaliūtė, Rūta; Žvirblys, Atas; Ananyevskaya, Elina; Motuzaitė Matuzevičiūtė, Giedrė (Danish Journal of Archaeology, 2023)
This article presents research results from the archaeological excavation in the territory of Dominikonų St. 11 in Vilnius Old Town. In order to present as thorough dietary reconstructions of people who lived here as possible, four groups of evidence were combined together: archaeological artifacts, historical datasets, zooarchaeological research and archaeobotanical investigation. The analyzed materials are covering a wide chronological range (between 15th and 18th century) allowing us to observe the dietary changes in relation to architectural development, spatial distribution. This research shows changes in human diet across time from pre-Palace human diet consisting of grain and cattle meat to imported oysters, veal, game, and wines during the Palace period.